The effect of liquidity risk, capital and third-party fund on bank performance with credit risk as intervening variable: Cases in conventional Bank in Indonesia - Sutrisno, Sutrisno (Jurnal Siasat Bisnis, 2025)
Purpose – this research examines the effect of liquidity risk as measured by the loan to deposit ratio (LDR), bank capital as measured by the capital adequacy ratio (CAR), credit risk as measured by non-performing loans (NPL) and third-party funds (TPF). on profitability as measured by return on assets (ROA). The research also tests whether credit risk can be an intervening variable in the influence of LDR, CAR and TPF on profitabilityDesign/methodology/approach – The population of this research is 42 conventional banks on the Indonesia Stock Exchange (BEI), with a sample of 24 banks taken using purposive sampling technique. The observation period is 4 years with quarterly data. Hypothesis testing uses multiple regression analysis tools with a significance level of 0.05Findings – The research results show that liquidity risk has a significant positive effect on profitability, credit risk has a significant negative effect on profitability. Meanwhile, capital and third-party funds have no effect on profitability. Another result turns out that credit risk can only be an intervening variable in the influence of liquidity risk on profitability.Research limitations/implications – This research only tested three independent variables and one intervening variable. Besides that, this research uses multiple regression analysis, so that future researchers can research further by adding variables that influence profitability and can use panel data regression analysis.Practical implications – It is hoped this research can be used by bank management in its efforts to increase profitability by considering four variables that influence it and shows the role of credit risk in mediating the influence of independent variables on profitability.Originality/value – The novelty in this research is including the role of credit risk as an intervening variable which is still rarely researched.